2017
DOI: 10.1093/cercor/bhw409
|View full text |Cite
|
Sign up to set email alerts
|

Orbitofrontal Cortex Neurons Respond to Sound and Activate Primary Auditory Cortex Neurons

Abstract: Sensory environments change over a wide dynamic range and sensory processing can change rapidly to facilitate stable perception. While rapid changes may occur throughout the sensory processing pathway, cortical changes are believed to profoundly influence perception. Prior stimulation studies showed that orbitofrontal cortex (OFC) can modify receptive fields and sensory coding in A1, but the engagement of OFC during listening and the pathways mediating OFC influences on A1 are unknown. We show in mice that OFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 32 publications
9
72
1
Order By: Relevance
“…The V1-projecting OFC neurons target all three subtypes of inhibitory interneurons in V1, similar to that found for OFC projections to auditory cortex 37 and cingulate cortex projections to V1 36 . We found that optogenetic stimulation of OFC neurons in vivo preferentially activated SST interneurons in V1.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The V1-projecting OFC neurons target all three subtypes of inhibitory interneurons in V1, similar to that found for OFC projections to auditory cortex 37 and cingulate cortex projections to V1 36 . We found that optogenetic stimulation of OFC neurons in vivo preferentially activated SST interneurons in V1.…”
Section: Discussionsupporting
confidence: 76%
“…Frontal top-down projections to sensory cortices are known to modulate sensory processing [35][36][37] , promote accurate perception 38 , and convey predictive signals 39,40 .…”
mentioning
confidence: 99%
“…A commonly used procedure to assess the magnitude of top-down mechanisms is to compare neural responsiveness during two different states of behavioral engagement (37,(44)(45)(46)(47)(48)(49). Specifically, top-down inputs are thought to actively modulate ACx responses during task performance (or "engagement") but not during nontask ("disengaged") listening sessions (50,51). Thus, the difference between engaged and disengaged sensitivity is a proxy for the strength of a top-down mechanism.…”
Section: Significancementioning
confidence: 99%
“…For our purposes, top-down refers to the functional influence of a higher-order brain region on neural activity in ACx, brought about by task engagement. Several plausible candidate regions may mediate this top-down effect, either in isolation or in concert with one another, including frontal cortex (50,51), nucleus basalis (73)(74)(75), locus coeruleus (76), ventral tegmental area (77,78), and multisensory cortex (17).…”
Section: Significancementioning
confidence: 99%
“…We know of no existing evidence that the prefrontal cortex influences responses in the IC. However, neurons in the orbitofrontal regions respond to sound and via descending connections influence sound processing in auditory cortex (Saunders et al, 1985;Fritz et al, 2010;Schneider et al, 2014;Winkowski et al, 2018). These prefrontal cortical regions have a central role in executive function and exert task-dependent influences on sensory processing (Öngür and Price, 2000).…”
Section: Auditory and Non-auditory Cortico-collicular Projectionsmentioning
confidence: 99%